Edge computing -- EDGE 2023 : 7th International Conference, held as part of the Services Conference Federation, SCF 2023 Shenzhen, China, December 17-18, 2023, Proceedings - EDGE (Conference) 2023 : Shenzhen, China); Feng, Jun; Jiang, Frank; Luo, Min, Ph.D.; Zhang, Liang-Jie; Services Conference Federation (2023 : Shenzhen, China) (Cham : Springer, 2024)
This book constitutes the refereed proceedings of the 7th International Conference on Edge Computing, EDGE 2023, held in Shenzhen, China, during December 17-18, 2023. The 8 full papers in this book were carefully reviewed and selected from 14 submissions. They were organized in topical sections as follows: Practice of Edge Computing, identify emerging research topics, and define the future of Edge Computing.
Research and Application of Low Voltage Distributed Power Supply Control System -- Optimized Edge-cCCN Based Model for the Detection of DDoS Attack in IoT Environment -- RuCIL: Enabling Privacy-Enhanced Edge Computing for Federated Learning -- Designing Blended Learning Activities in the Era of Artificial Intelligence -- Data Standard Construction -- Construction and Application of Enterprise Data Assets based on Data Label System -- Secure and Fast Query Approach for High-precision Multi-dimensional Satellite Remote Sensing Data -- Data Operation and Management Practices in Ping An Group. .
Includes author index.
Online resource; title from PDF title page (SpringerLink, viewed January 24, 2024).
Keywords: Edge computing -- Congresses